Semantic deficits in ALS related to right lingual/fusiform gyrus network involvement - Ogura, Aya (EBioMedicine, 2019)
BACKGROUND: The clinicopathological continuity between amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) is well known. Although ALS demonstrates language symptoms similar to FTLD, including semantic dementia, word reading impairments in ALS have not been well studied. “Jukujikun” are Kanji-written words with irregular pronunciation comparable to “exception words” and useful for detecting semantic deficits in Japan. We conducted a cross-sectional study to investigate Jukujikun reading impairments and related network changes in ALS. METHODS: We enrolled 71 ALS patients and 69 healthy controls (HCs). Age-, sex-, and education matched HCs were recruited from another cohort study concurrently with patient registration. We examined neuropsychological factors including low frequency Jukujikun reading. We performed resting-state functional magnetic resonance imaging with voxel-based graph analysis on a subset of participants who agreed. FINDINGS: Low frequency Jukujikun score was decreased in ALS (15·0[11·0–19·0](median[25–75 percentile])) compared with HCs (19·0[17·3–20·0]) (p < 0·001, effect size = 0·43). Fifty-two percent of ALS (N = 37) with low frequency Jukujikun score ≤ 5th percentile of HCs was classified as ALS with positive Jukujikun deficit (ALS-JD+). Compared with HCs, ALS-JD+ showed decreased degree centrality in the right lingual/fusiform gyrus, where connectivities with regions associated with word perception, semantic processing, or speech production were decreased. They also showed increased degree centrality in the left inferior/middle temporal gyrus, associated with increased connectivities involving semantic processing. INTERPRETATION: Dysfunction of the “hub” in the right lingual/fusiform gyrus can affect semantic deficit in ALS. Considering neuropsychological symptoms as network impairments is vital for understanding various diseases. FUND: MHLW and MEXT, Japan.